Growth and yield performance of hybrid tomato (Solanum lycopersicum L.) lines at Parwanipur, Bara, Nepal - Gurung, Suraj; Adhikari, Prabin; Giri, Kushal; Gotame, Tek Prasad; Shrestha, Surendra Lal (Journal of Agriculture and Natural Resources, 2020)
An experiment was conducted to evaluate the performance of hybrid tomato lines on growth and yield performance at Regional Agriculture research Station (RARS), Parwanipur, Nepal during end of September, 2018 to April, 2019. The experiment was laid out in randomized complete block design (RCBD) with seven hybrid tomato lines as treatments and three replications. The tested lines included Srijana and Dalila as check varieties and other lines, developed by crossing HRA and HRD lines which showed better performance under late blight conditions. HRA 20× HRD 1 showed significantly higher plant height (110.67 cm) which was statistically at par with genotype HRA 14× HRD 7. The highest number of fruits per plant (69) was recorded from Srijana whereas the lowest number of fruits per plant (37) was recorded from cv. HRA20 × HRD1. The fruit yield of the lines ranged from 50.54 t/ha to 32.2 t/ha with Srijana having the highest yield and HRA 20× HRD 1 as the lowest. Similar results were shown regarding the marketable fruit yield. However, the highest individual fruit weight (34.67g) was recorded in HRA 14× HRD 7 and the least fruit weight was recorded in Srijana (24.22 g). Results showed that the maximum TSS (5.53 0Brix) was recorded from Dalila which was similar as Srijana. Hence, the overall performance of Srijana was recorded superior regarding both quantitative and qualitative suggesting Srijana as the recommended variety in the given domain. Here authors concluded that Srijana is still a comparatively better hybrid variety in Nepal.